2018
DOI: 10.1002/jcb.26364
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived exosomes: Potential biomarker or therapeutic target in breast cancer?

Abstract: Exosomes are released by normal and tumour cells, including those involved in breast cancer, and provide a means of intercellular communications. Exosomes with diameters ranging between 30-150 nm are involved in transferring biological information, via various lipids, proteins, different forms of RNAs, and DNA from one cell to another, and this can result in reprogramming of recipient cell functions. These vesicles are present in all body fluids, for example, blood plasma/serum, semen, saliva, cerebrospinal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…In milk, microRNA expression was related to mammary gland conditions, including infections (Iannaccone et al., ; Lai et al., , ; Sun et al., ), cancer (Decmann et al., ; Do Canto et al., ; Hesari et al., ), pregnancy and lactation status (Carney et al., ; Perri et al., ; Schanzenbach et al., ), and maternal diet (Chen et al., ). Therefore microRNAs in milk were studied for their potential as biomarkers (Gustafson, Tyryshkin, & Renwick, ; Melnik & Schmitz, ) such as quality controls of commercial milk (Oh et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…In milk, microRNA expression was related to mammary gland conditions, including infections (Iannaccone et al., ; Lai et al., , ; Sun et al., ), cancer (Decmann et al., ; Do Canto et al., ; Hesari et al., ), pregnancy and lactation status (Carney et al., ; Perri et al., ; Schanzenbach et al., ), and maternal diet (Chen et al., ). Therefore microRNAs in milk were studied for their potential as biomarkers (Gustafson, Tyryshkin, & Renwick, ; Melnik & Schmitz, ) such as quality controls of commercial milk (Oh et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Although, epidemiological correlations for whole milk consumption and BC are less established than those for whole milk intake and PCa, tumor-derived exosomes as well play a key role in tumor initiation and progression in BC [344][345][346][347][348][349]. The widespread post-transcriptional regulatory role of miRs is of recent interest in estrogen receptor (ER)-positive BC, comprising about 65%-70% of BCs [350].…”
Section: Breast Cancermentioning
confidence: 99%
“…Human urine is one of the most useful body biofluids for routine testing. A number of studies have suggested that urine could contain potential biomarkers for breast cancer screening, ranging from metabolome profiling and proteomic profiling to exosomic analysis [ 147 , 148 , 149 , 150 ].…”
Section: Non-blood-based Biomarkersmentioning
confidence: 99%